PERGULATAN MAHASISWI BERCADAR DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI DI JAWA TIMUR : A STUDY OF THE MUSLIMAH STUDENTS AT STATE ISLAMIC UNIVERSITY IN EAST JAVA - Za'imatil Ashfiya (Al'Adalah, 2022)
In a country where most of the population is Muslim, wearing a face veil is not new. However, the face veil for Muslimah students in Indonesia is still polemic because it seems old-fashioned, rigid, and underestimated by some people, so they are considered Islamic fanatics, radicalized Muslims, extremists, or terrorists. Several state Islamic universities govern how to dress on campus. This qualitative research aims to reveal the motivations and struggles of Muslimah students in wearing face veils at UIN Sunan Ampel and IAIN Jember (now: UIN Kiai Haji Achmad Siddiq Jember) during 2019-2020. Therefore, the researcher also used interview and observation methods to obtain the data. The study results are the Muslimah students' motivation to wear the face veil because of the need for self-security from men and the need to be respected (need for self-esteem). The struggles carried out by the informants are different from the motivation and acceptance of the milieu. The higher the motivation to wear the face veil, the stronger they maintain it. Although they do not support the milieu, a strong motivation will defend their honor (muru'ah). In addition to motivation, the milieu is also significant. The more tolerated the milieu, the easier the struggle made by the informants.